Characteristics and outcomes in bladder Leiomyoma management: a systematic review of case reports and case series from the past 20 years - Johannes Cansius Prihadi; Antoninus Hengky; Stevan Kristian Lionardi; Sean Peter Haruman (BMC Urology)
Abstract Introduction Bladder leiomyomas (LM) are uncommon, non-cancerous growths that originate from the smooth muscle cells of the bladder and constitute 0.5% of bladder tumor cases. This review aims to compile existing data and present a summary of bladder leiomyomas’ characteristics, management, and related outcomes. Method We conducted systematic review of studies that investigated bladder leiomyoma. Case studies or series describing individuals with bladder leiomyoma who underwent surgery and the outcomes were included. Four databases were used in our literature search, which was carried out until January 2024: PubMed, Proquest, EBSCOHost, and Google Scholar. We utilized MeSH terms such as “leiomyoma,” “urinary bladder,” and looked for synonyms of “bladder leiomyoma” in free text. Results A total of 99 studies with 119 patients were included. Most reported bladder leiomyoma cases were female, accounting for 79.0% of all cases. While symptomatic patients primarily presented with lower urinary tract symptoms (LUTS) (59.7%), hematuria (24.4%), acute urine retention (11.8%), and about 16.8% of cases were incidentally detected. Storage-related symptoms were the most common LUTS (37.0%). Different diagnostic techniques were used, frequently combining CT (Computed Tomography), MRI (Magnetic Resonance Imaging), USG (Ultrasonography), and/or cystoscopy. Bladder leiomyomas were commonly found on the left lateral wall (26.9%) and the bladder neck (17.6%). In more than half of the cases (52.1%) the treatment techniques used were transurethral resection (TURBt/TUR). Fifteen out of 119 cases (12.6%) had recurrence or remain symptomatic. Symptomatic symptoms at first presentation and extended location are frequently found among recurrent or symptomatic cases after first management. Conclusion Management of bladder leiomyoma should focus on the relief of symptoms and recurrence and be personalized based on the tumor characteristics, patient symptoms, and surgeon’s expertise. Further investigation is necessary to fully understand the best course of treatment and long-term results for bladder leiomyomas. In particular, prospective trials with bigger participant pools and meticulously controlled factors should be the main emphasis of this research.